TES HIV/AIDS TERHADAP CALON PENGANTIN DALAM PERSPEKTIF HUKUM ISLAM - Asep Saepullah; Mohammad Rana; Irfan Dzikri Abdillah, (IAIN Syekh Nurjati Cirebon, 2019)
Marriage is a sacred event in the course of one's life and the quality of a marriage is largely determined by the readiness and maturity of the two brides to prepare and manage household life towards the creation of a family that is sakinah, mawaddah and full of grace. For that it is necessary to first recognize the new life that will be experienced later to prospective husbands or wives, so that in time it can anticipate problems that arise later can be minimized, for that brides really need to take a brief debriefing about HIV/AIDS and carry out testing HIV/AID in the form of a bride and groom course which is one of the important and strategic efforts.This research aims to answer the questions that formulate the problem: How to examine HIV/AIDS tests on brides in KUA, Lemahwungkuk District, Cirebon City and How to Review Islamic Law on HIV/AIDS testing for brides conducted in KUA, Lemahwungkuk District, Cirebon City